2017
DOI: 10.1108/arla-08-2015-0190
|View full text |Cite
|
Sign up to set email alerts
|

Internal marketing and customer-contact employees’ attitudinal outcomes

Abstract: Purpose Higher education institutions, particularly in the case of public universities, face the challenge of creating more value in an environment of increasing requirements and limitations. The purpose of this paper is to explore the relation of internal marketing (IM) with employees’ attitudinal outcomes, which aim to stimulate and retain motivated and customer-conscious contact employees. Design/methodology/approach Survey data of 94 customer-contact employees in a public higher education institution wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
2
9
0
Order By: Relevance
“…The one of the results of this paper confirmed that internal green marketing affects organizational identification (in this case managers' organizational identification in the agribusiness sector), similar to the impact of green marketing on employees' organizational identification in the service sector (Boukis et al, 2015;Hernández-Díaz et al, 2017). This result confirmed the relevance of an implementation of this concept and its effects in the sector where services are not the primary activity.…”
Section: Discussionsupporting
confidence: 79%
“…The one of the results of this paper confirmed that internal green marketing affects organizational identification (in this case managers' organizational identification in the agribusiness sector), similar to the impact of green marketing on employees' organizational identification in the service sector (Boukis et al, 2015;Hernández-Díaz et al, 2017). This result confirmed the relevance of an implementation of this concept and its effects in the sector where services are not the primary activity.…”
Section: Discussionsupporting
confidence: 79%
“…Employees should be trained and developed in such a way that they can understand the goals of the organization so that they can perform their tasks to the best of their ability. Among the internal marketing definitions mentioned is that the business focuses on training in addition to focusing on customers (Hernandez-Diaz, et al, 2017). Statistical analyzes of data show a positive relationship between training and development programs and salesperson motivation (Hernandez-Diaz et al, 2017).…”
Section: Theoretical Basismentioning
confidence: 99%
“…Among the internal marketing definitions mentioned is that the business focuses on training in addition to focusing on customers (Hernandez-Diaz, et al, 2017). Statistical analyzes of data show a positive relationship between training and development programs and salesperson motivation (Hernandez-Diaz et al, 2017).…”
Section: Theoretical Basismentioning
confidence: 99%
“…The primary stakeholders of a service brand are its employees (Brexendorf and Kernstock, 2007), who are not merely internal customers (Mohrw‐Jackson, 1991). The information employees obtain during their work experiences and interactions with the organization from their personal perceptions, attitudes and behaviors toward the brand, which manifest outwardly as brand promises (King and Grace, 2009; Supornpraditchai et al , 2007; Hernández-Díaz et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have also asserted that a corporation that enhances its EBBE will be able to lower recruiting costs (Morehart, 2001), improve employee performance (Kirnan et al , 1989), reduce employee turnover (Supornpraditchai et al , 2007) and create further economic benefits (Morehart, 2001). Thus, the enhancement of EBBE could be an important topic for in-depth investigation in the fields of brand and internal marketing (Supornpraditchai et al , 2007; Baumgarth and Schmidt, 2010; King and Grace, 2010; Hernández-Díaz et al , 2017; King et al , 2012).…”
Section: Introductionmentioning
confidence: 99%